2002
DOI: 10.1007/s00429-002-0262-9
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and morphometric changes in the rat kidney during postnatal development

Abstract: We have investigated the temporal maturation of the rat kidney during the postnatal developmental period. As a result, we observed the following: an active process of cortical cell proliferation and differentiation occurs as late as day 20. The medulla is the most immature zone at birth and displays the greatest morphological changes during this period. At birth, no distinction exists between inner and outer medulla, and the outer and inner strip of the outer medulla can be distinguished as late as day 30. Rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
60
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 15 publications
9
60
0
2
Order By: Relevance
“…21,36 Corroborating previous findings, 27,28 the present study demonstrated that, although the overall, pressor, and depressor slopes of the acute RAP-RIHP relationship are not different between strains, there is a rightward shift toward a greater RAP in 4-week-old SHRs relative to WKY rats. This finding not only supports the proposed cascade of players in pressurenatriuresis (ie, medullary blood flow, RIHP, urine flow, and sodium excretion) 37 but also, more importantly, the hypothesis that renal medullary vascular resistance properties are elevated in young SHRs 28,34 after completion of postnatal renal organogenesis (ie, postnatal day 30). 28,34 This notion is further supported by the moment-to-moment nature of RIHP responses (ie, Ͻ2 s) to changes in RAP in 4-week-old rats.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…21,36 Corroborating previous findings, 27,28 the present study demonstrated that, although the overall, pressor, and depressor slopes of the acute RAP-RIHP relationship are not different between strains, there is a rightward shift toward a greater RAP in 4-week-old SHRs relative to WKY rats. This finding not only supports the proposed cascade of players in pressurenatriuresis (ie, medullary blood flow, RIHP, urine flow, and sodium excretion) 37 but also, more importantly, the hypothesis that renal medullary vascular resistance properties are elevated in young SHRs 28,34 after completion of postnatal renal organogenesis (ie, postnatal day 30). 28,34 This notion is further supported by the moment-to-moment nature of RIHP responses (ie, Ͻ2 s) to changes in RAP in 4-week-old rats.…”
Section: Discussionsupporting
confidence: 74%
“…This finding not only supports the proposed cascade of players in pressurenatriuresis (ie, medullary blood flow, RIHP, urine flow, and sodium excretion) 37 but also, more importantly, the hypothesis that renal medullary vascular resistance properties are elevated in young SHRs 28,34 after completion of postnatal renal organogenesis (ie, postnatal day 30). 28,34 This notion is further supported by the moment-to-moment nature of RIHP responses (ie, Ͻ2 s) to changes in RAP in 4-week-old rats. Specifically, it appears that there is an underlying vascular basis for this component of the pressure-natriuresis mechanism, because it is unlikely that slower-acting neurohumoral mechanisms play a role in altering the acute functioning of this relationship.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The last nephron anlages to be formed develop into functional nephron by 10 days after birth. 14,15 Rats enter puberty at the age of 4 weeks and reach sexual maturity at 8 weeks. We used an in situ probe specific to the transgene as well as a probe that detected both the transgenic and endogenous Anks6 mRNA.…”
Section: Anks6mentioning
confidence: 99%
“…9 We tracked the morphogenesis of the renal medulla into adult life. At 30 to 33 weeks of age, the renal papilla remained hypoplastic (Figures 3, A and B), but aquaporin 2 (AQP2) expression was normal in residual papillary collecting ducts (Supplemental Figure 2).…”
mentioning
confidence: 99%